THE ROLE OF THE DYNAMICS STUDENT PRESS ORGANIZATION IN IMPROVING THE SOFT SKILLS OF UIN SU COMMUNICATION SCIENCE STUDENTS - Alya Sherin; Nabilah Ramadani; Naufal Dzakwan Arkam; Umaira Sabila (OPINI: Journal of Communication and Social Science, 2024)
Student press organizations are a forum for students to develop various skills outside formal academic activities. Involvement in this organization provides opportunities for students to learn through direct practice and intensive social interaction. This research aims to explore how student press organizations can play a role in improving students' soft skills by using social learning theory and social constructivism approaches. This research uses a descriptive qualitative method by interviewing sources who are active in student press institutions. The results of this research show the important role of LPM Dinamika in helping improve the soft skills of Communication Science students at the State Islamic University of North Sumatra through various activities and work programs.